NT-pro-BNP levels in patients with acute pulmonary embolism are correlated to right but not left ventricular volume and function - Pasha, Sharif M.; Klok, Frederikus A.; van der Bijl, Noortje; de Roos, Albert; Kroft, Lucia J. M.; Huisman, Menno V. (Thrombosis and Haemostasis, 2012)
N-terminal pro-Brain Natriuretic Peptide (NT-pro-BNP) is primarily secreted by left ventricular (LV) stretch and wall tension. Notably, NT-pro-BNP is a prognostic marker in acute pulmonary embolism (PE), which primarily stresses the right ventricle (RV). We sought to evaluate the relative contribution of the RV to NT-pro-BNP levels during PE. A posthoc analysis of an observational prospective outcome study in 113 consecutive patients with computed tomography (CT)-proven PE and 226 patients in whom PE was clinically suspected but ruled out by CT. In all patients RV and LV function was established by assessing ECG-triggered-CT measured ventricular end-diastolic-volumes and ejection fraction (EF). NT-pro-BNP was assessed in all patients. The correlation between RV and LV end-diastolic-volumes and systolic function was evaluated by multiple linear regression corrected for known con-founders. In the PE cohort increased RVEF (β-coefficient (95% confidence interval [CI]) –0.044 (± –0.011); p<0.001) and higher RV enddiastolic-volume (β-coefficient 0.005 (± 0.001); p<0.001) were significantly correlated to NT-pro-BNP, while no correlation was found with LVEF ( β-coefficient 0.005 (± 0.010); p=0.587) and LV end-diastolic-volume (β-coefficient –0.003 (± 0.002); p=0.074). In control patients without PE we found a strong correlation between NT-pro-BNP levels and LVEF ( β-coefficient –0.027 (± –0.006); p<0.001) although not LV enddiastolic-volume (β-coefficient 0.001 (± 0.001); p=0.418). RVEF (β-co-efficient –0.002 (± –0.006); p=0.802) and RV end-diastolic-volume (β-coefficient <0.001 (± 0.001); p=0.730) were not correlated in patients without PE. In PE patients, lower RVEF and higher RV end-diastolic-volume were significantly correlated to NT-pro-BNP levels as compared to control patients without PE. These observations provide patho-physiological ground for the well-known prognostic value of NT-pro-BNP in acute PE.
Keywords: Venous thrombosis; heart; cardiac biomarker